Influence of the Laurentide Ice Sheet and relative sea‐level changes on sediment dynamics in the Estuary and Gulf of St. Lawrence since the last deglaciation - Casse, Marie; Montero-Serrano, Jean-Carlos; St-Onge, Guillaume (Boreas, 2017)
Physical properties, grain size, bulk mineralogy, elemental geochemistry and magnetic parameters of three sediment piston cores recovered in the Laurentian Channel from its head to its mouth were investigated to reconstruct changes in detrital sediment provenance and transport related to climate variability since the last deglaciation. The comparison of the detrital proxies indicates the succession of two sedimentary regimes in the Estuary and Gulf of St. Lawrence (EGSL) during the Holocene, which are associated with the melting history of the Laurentide Ice Sheet (LIS) and relative sea‐level changes. During the early Holocene (10–8.5 cal. ka BP), high sedimentation rates together with mineralogical, geochemical and magnetic signatures indicate that sedimentation in the EGSL was mainly controlled by meltwater discharges from the local retreat of the southeastern margin of the LIS on the Canadian Shield. At this time, sediment‐laden meltwater plumes caused the accumulation of fine‐grained sediments in the ice‐distal zones. Since the mid‐Holocene, postglacial movements of the continental crust, related to the withdrawal of the LIS (c. 6 cal. ka BP), have triggered significant variations in relative sea level (RSL) in the EGSL. The significant correlation between the RSL curves and the mineralogical, geochemical, magnetic and grain‐size data suggest that the RSL was the dominant force acting on the sedimentary dynamics of the EGSL during the mid‐to‐late Holocene. Beyond 6 cal. ka BP, characteristic mineralogical, geochemical, magnetic signatures and diffuse spectral reflectance data suggest that the Canadian Maritime Provinces and western Newfoundland coast are the primary sources for detrital sediments in the Gulf of St. Lawrence, with the Canadian Shield acting as a secondary source. Conversely, in the lower St. Lawrence Estuary, detrital sediments are mainly supplied by the Canadian Shield province. Finally, our results suggest that the modern sedimentation regime in the EGSL was established during the ...